2013
DOI: 10.1002/ab.21501
|View full text |Cite
|
Sign up to set email alerts
|

A quick assessment tool for human‐directed aggression in pet dogs

Abstract: Many test series have been developed to assess dog temperament and aggressive behavior, but most of them have been criticized for their relatively low predictive validity or being too long, stressful, and/or problematic to carry out. We aimed to develop a short and effective series of tests that corresponds with (a) the dog's bite history, and (b) owner evaluation of the dog's aggressive tendencies. Seventy-three pet dogs were divided into three groups by their biting history; non-biter, bit once, and multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
1
26
1
Order By: Relevance
“…Since the situation in which our stimuli were photographed is unknown and dog aggression is often exhibited in fearful situations [72], it is likely that some of the images of Threatening Dogs capture also fear. However, disgust provoked by a disliked taste represents a rather distinct emotion from aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Since the situation in which our stimuli were photographed is unknown and dog aggression is often exhibited in fearful situations [72], it is likely that some of the images of Threatening Dogs capture also fear. However, disgust provoked by a disliked taste represents a rather distinct emotion from aggression.…”
Section: Discussionmentioning
confidence: 99%
“…manifested in biting history) directed towards the owner or family members remains undetected (e.g. [ 24 ]), although this is a crucial aspect of the dog's behaviour. Marder et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this test, the dog was tethered to a tree or fence pole by a 2 m long, sturdy rope (for detailed method see [ 24 , 30 ]). On one arm, the owner wore an artificial hand (casted from gypsum and covered with a cloth-glove, providing a life-like appearance to it), while also wearing a pressed paper forearm-guard under his/her sleeve, for further protection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We derived the basic emotional behaviours from observations of previous ethological studies of pet dogs in situations when a) dogs were observed in an emotion evoking context, b) the direction and speed of dogs' movements, changes in their postures and the position of body parts, and vocalisations could be assessed. The following concrete contexts were adopted: Joy: 'greeting the owner' (Konok, Dóka, & Miklósi, 2011;Topál, Miklósi, Csányi, & Dóka, 1998), and 'going for a walk' (Pongrácz et al, 2005); Anger: 'facing a threatening stranger' (Vas, Topál, Gácsi, Miklósi, & Csányi, 2005), 'watching a stranger through the fence' (Pongrácz et al, 2011); Fear: 'facing a threatening stranger' (Klausz, Kis, Persa, Miklósi, & Gácsi, 2014); Sadness: 'separation from owner' (Pongrácz et al, 2011;Topál et al, 1998), 'being scolded by owner' (Hecht et al, 2012); Neutral: 'mobile owner' task during which the owner moves around in a room without initiating interaction with or looking at the dog (Faragó, Miklósi, Korcsok, Száraz, & Gácsi, 2014).…”
Section: Establishment Of the Emotional Behavioursmentioning
confidence: 99%